Age-period-cohort analysis of intestinal obstruction incidence trends among Chinese residents from 1992 to 2021 - Guilian LAN; Yao WU (Zhongguo gonggong weisheng)
ObjectiveTo understand the incidence trends of intestinal obstruction in Chinese residents from 1992 to 2021 and to provide a scientific basis for formulating precise prevention and control measures for intestinal obstruction. MethodsData on the number of cases, incidence rate, and age-standardized incidence rate (ASIR) of intestinal obstruction in Chinese residents from 1992 to 2021 were extracted from the Global Burden of Disease Study 2021 (GBD 2021) database. Descriptive analysis and Joinpoint regression models were used to evaluate the trends in the incidence of intestinal obstruction in Chinese residents and calculate the average annual percentage change (AAPC). The age-period-cohort (APC) model was used to assess the age, period, and cohort effects on the risk of intestinal obstruction in Chinese residents. ResultsThe incidence rates of intestinal obstruction in the total population, male residents, and female residents of China increased from 204.411/100 000, 227.272/100 000, and 179.973/100 000 in 1992 to 231.393/100 000, 259.508/100 000, and 201.923/100 000 in 2021, respectively. The ASIR decreased from 220.367/100 000, 247.453/100 000, and 192.676/100 000 in 1992 to 198.500/100 000, 226.548/100 000, and 170.553/100 000 in 2021, respectively. The AAPC values of ASIR were –0.355%, –0.302%, and –0.410% (all P<0.01), respectively. The APC model analysis showed that the age effect of the incidence of intestinal obstruction in the total population, male residents, and female residents of China showed an overall upward trend with increasing age. The age effect coefficients increased from 0.126, 0.103, and 0.183 for ages 0–4 years to 0.413, 0.725, and 0.453 for ages ≥95 years, respectively. The period effect of the incidence of intestinal obstruction in the total population, male residents, and female residents of China showed an overall downward trend over time. The period effect coefficients decreased from 1.000, 1.008, and 0.993 for the period 1992–1996 to 0.942, 0.958, and 0.920 for the period 2017–2021, respectively. The cohort effect of the incidence of intestinal obstruction in the total population, male residents, and female residents of China showed a trend of first increasing and then decreasing. The cohort effect coefficients for the total population increased from 0.591 for the 1897–1901 cohort to 1.079 for the 1942–1946 cohort and then decreased to 0.718 for the 2017–2021 cohort. The cohort effect coefficients for male residents increased from 0.640 for the 1897–1901 cohort to 1.076 for the 1947–1951 cohort and then decreased to 0.716 for the 2017–2021 cohort. The cohort effect coefficients for female residents increased from 0.638 for the 1897–1901 cohort to 1.142 for the 1927–1931 cohort and then decreased to 0.706 for the 2017–2021 cohort. ConclusionsThe ASIR of intestinal obstruction in Chinese residents showed an overall downward trend from 1992 to 2021, but it is still necessary to strengthen the prevention and control of intestinal obstruction in male and elderly populations.